ANALISIS KEBUTUHAN TES HASIL BELAJAR MATEMATIKA SEKOLAH DASAR BERKARAKTERISTIK HOTS BERBENTUK PILIHAN GANDA - Ariyana, I Komang Sesara (Unika Santu Paulus Ruteng, 2020)
This study aimed to describe the needs analysis of the mathematics learning outcomes test characterized by HOTS (higher-order thinking skills) in the form of multiple-choice for fifth-grade students in Singaraja City, Buleleng Regency, Bali Province. This research was conducted at several elementary schools in the city of Singaraja. The study population was all elementary school mathematics teachers in Singaraja City. The sample used was a purposive sample, that was, by determining respondents from selected schools based on several characteristics. These characteristics were A) inside and outside the city, B) favorite and non-favorite, C) public and private, and D) public and Muslim. The samples obtained were 7 (seven) elementary schools. The data collection method was a questionnaire method. The questionnaire in this study produced both quantitative and qualitative data. Quantitative data in the form of nominal data from responses “yes” and “no”, while qualitative data in the form of comments based on responses “yes” or “no” provided. This was done by researchers in order to draw stronger and more complete conclusions. Quantitative data analysis techniques used descriptive statistics, while qualitative data analysis techniques use descriptive analysis. Based on the results of the study, it could be concluded that the teacher requires an elementary mathematics learning achievement test characterized by HOTS. The results of this study were used to develop a mathematics learning outcomes test characterized by HOTS in the form of multiple choice.